2016
DOI: 10.1590/s0100-204x2016001100011
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial do intervalo hídrico ótimo de solos cultivados em sistema plantio direto

Abstract: Resumo -O objetivo deste trabalho foi avaliar a acurácia das regressões que definem os limites do intervalo hídrico ótimo e a validade do uso deste indicador ao se considerar a variabilidade espacial de lavouras sob sistema plantio direto. Foram coletadas 100 amostras de solo com estrutura preservada, em áreas com dimensões de 10x10 m, em Latossolo Vermelho distrófico, Nitossolo Vermelho distroférrico e Latossolo Vermelho aluminoférrico, manejados sob sistema plantio direto. Determinaram-se porosidade de aeraç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Dias et al (2016), working with sugarcane, finding that these typical results due to high soil bulk density or compacted soils, relating to high water content so that the PR does not reach the limiting value. Several authors also observed that the influence of SW RP to the LLWR of soil in different soil management systems (Leão et al, 2004;Moreira et al, 2014;Silva et al, 2017;Fashi et al, 2017) and texture classes (Pereira et al, 2015;Dias et al, 2016;Klein et al, 2016).…”
Section: Least Limiting Water Rangementioning
confidence: 94%
See 4 more Smart Citations
“…Dias et al (2016), working with sugarcane, finding that these typical results due to high soil bulk density or compacted soils, relating to high water content so that the PR does not reach the limiting value. Several authors also observed that the influence of SW RP to the LLWR of soil in different soil management systems (Leão et al, 2004;Moreira et al, 2014;Silva et al, 2017;Fashi et al, 2017) and texture classes (Pereira et al, 2015;Dias et al, 2016;Klein et al, 2016).…”
Section: Least Limiting Water Rangementioning
confidence: 94%
“…Critical value selection of the PR interferes with the range of the LLWR and the value of the critical soil bulk density -SCD (Moreira et al, 2014). Klein et al (2016) state that the use of the value of 2.0 MPa as restrictive under no-tillage appears to be inadequate, once crops seek ways for lower restriction for their growth cycle, thus, under these systems largest values of PR are commonly observed. Several authors studying the LLWR consider that a different critical PR of 2.0 MPa (Tormena et al, 1998;Betioli Junior et al, 2012;Araújo et al, 2013;Moreira et al, 2014).…”
Section: Least Limiting Water Rangementioning
confidence: 99%
See 3 more Smart Citations